Exploring First Interactions Between Ostreid Herpesvirus 1 (OsHV-1) and Its Host, Crassostrea gigas: Effects of Specific Antiviral Antibodies and Dextran Sulfate - Martenot, Claire; Faury, Nicole; Morga, Benjamin; Degremont, Lionel; Lamy, Jean-Baptiste; Houssin, Maryline; Renault, Tristan (Frontiers in Microbiology, 2019)
Viral entry mechanisms of herpesviruses constitute a highly complex process which implicates several viral glycoproteins and different receptors on the host cell surfaces. This initial infection stage was curently undescribed for Ostreid herpes virus 1 (OsHV-1), a herpesvirus infecting bivalves including the Pacific oyster, Crassostrea gigas. To identify OsHV-1 glyproteins implicated in the attachement of the virus to oyster cells, three viral putative membrane proteins, encoded by ORF 25, 41, and 72, were selected and polyclonal antibodies against these targets were used to explore first interactions between the virus and host cells. In addition, effects of dextran sulfate, a negative charged sulfated polysaccharide, were investigated on OsHV-1 infection. Effects of antiviral antibodies and dextran sulfate were evaluated by combining viral DNA and RNA detection in spat (in vivo trials) and in oyster haemolymph (in vitro trials). Results showed that viral protein encoded by ORF 25 appeared to be involved in interaction between OsHV-1 and host cells even if other proteins are likely implicated, such as proteins encoded by ORF 72 and ORF 41. Dextran sulfate at 30µg/mL reduced significantly the spat mortality rate in the experimentally conditions. Taken together, these results contribute to better understanding the pathogenesis of the viral infection, especially during the first stage of the OsHV-1 infection and open the way towards new approaches to control OsHV-1 infection in confined facilities